The Export-Led Growth Nexus in an Oil-Dominant Economy: Aggregated and Disaggregated Analysis - Joshua, Udi; Olajide, Afolabi Lukman; Gündüz, Selim; Cavdar, Seyma Caliskan; Sahin, Zekeriya; Bekun, Festus Victor (International Journal of Economics and Financial Issues, 2025)
The Keynesian theory of national income asserts that an increase in exports will enhance output performance significantly. Standing on this premise, this study seeks to validate the reality of export-led growth hypothesis in Nigeria by disaggregating export into oil and non-oil exports. Using Auto regressive distributed lag (ARDL) method to estimate time series data from 1981 to 2019. Empirical finding reveals evidence of export-led growth nexus for both the aggregated and disaggregated exports. Further results prove the existence of FDI-led growth nexus as well as saving-induced growth hypothesis. In contrast, import demonstrates a harmful relationship with economic growth. Thus, this study recommends an expansion of the export base of the country, particularly the non-oil sector, to enable her generate more foreign earnings. Domestic saving should be encouraged to improve the availability of investment funds for business expansion. A critical suggestion is made for the government to curtail importation especially for goods with domestic substitutes.